Joint production, externalities, and the regulation of production networks - Baumgärtner, Stefan; Jöst, Frank (Environmental & resource economics, 2000)
Real production systems are often vertically integrated in thesense that one production process uses the unwanted joint product of another production process as input.This interrelationship links in a non-obvious way the different negative externalities stemming from theproduction processes. An empirical example is the sulphuric acid industry. Our model of a vertically integratedproduction system shows how internalising one currently existing externality may create another externalitywhich has thus far not been existent. We also discuss how environmental policy could deal with this problemwhen regulating integrated production systems.
In: Environmental & resource economics
Keywords: Aufsatz in Zeitschrift